The Weakness Of The Law In The Republic Of Indonesia Number 18 Year 2003 On The Advocate - Sofyan Wimbo Agung Pradnyawan (Legal Standing : Jurnal Ilmu Hukum, 2017)
This article intends to analyze the use of the jury system in the criminal justice system of Indonesia, jury is a form of lay participation or the participation of lay that community of professional non-law in the judiciary, to make decisions which provide a more fulfilling sense of justice in society, in order to avoid the role of judges is absolute in the criminal justice process, in the legal system of modern states today dichotomy between legal systems tradition of common law or civil law is fading and towards the tendency to mix both the legal system in order to find substantive justice in the judicial process. Indonesia never make changes conceptually to the criminal justice system, so that the judicial process drab dominated the role of judges is great where law and justice seems to be the monopoly of a judge, the role of judges becomes absolute in determining aspects of the facts (fact finding) and the legal aspect in judge, legal research using law approach, conceptual, and comparative law. The results of this study is that morality is the essence of a sense of justice in society, morality can not be separated from the law, because morality is is what is considered correct by the general public, so the public will view the law as something that has no authority and can not be trusted, when morality is left in any decision of the judge in criminal justice. Entering jury in the justice system is able to raise the level of public confidence in the legal and judicial institutions that exist, because the inclusion of jury in the criminal justice system to prosecute in the aspect of fact (fact finding) addition will ease the task of the judge also made aspects of morality local is the living law in automatically entered in every decision, every decision so it is possible to better meet the sense of justice in society.